1984
DOI: 10.1029/jc089ic03p03689
|View full text |Cite
|
Sign up to set email alerts
|

A model function for ocean radar cross sections at 14.6 GHz

Abstract: The relationship between the ocean's normalized radar cross section (NRCS) at 14.6 GHz and the surface wind vector is derived using the 3 months of Seasat microwave scatterometer (SASS) measurements. The derivation is based on the statistics of the SASS observations, and no in situ measurements are required, other than a mean global wind speed, which comes from climatology. The frequency distribution of the global wind vectors observed by SASS is assumed to be a bivariate normal probability function. A NRCS mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
105
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 256 publications
(105 citation statements)
references
References 16 publications
0
105
0
Order By: Relevance
“…Thus dependence of the histogram of wind speeds on incidence angle is investigated in order to assess self-consistency of NSCAT wind speeds. In the SASS 2 model function, which has been used as the tentative prelaunch model function to produce NSCAT preliminary science products, an exponential relation between the wind speed at a height of 19.5 m and the radar cross section is assumed [Wentz et al, 1984]. At very low wind ranges, however, radar backscattering from the sea surface might be much weaker than that predicted by the exponential relation throughout all wind speed ranges.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Thus dependence of the histogram of wind speeds on incidence angle is investigated in order to assess self-consistency of NSCAT wind speeds. In the SASS 2 model function, which has been used as the tentative prelaunch model function to produce NSCAT preliminary science products, an exponential relation between the wind speed at a height of 19.5 m and the radar cross section is assumed [Wentz et al, 1984]. At very low wind ranges, however, radar backscattering from the sea surface might be much weaker than that predicted by the exponential relation throughout all wind speed ranges.…”
Section: Datamentioning
confidence: 99%
“…Wind vectors contained in the preliminary data products are retrieved using the prelaunch geophysical model function, SASS 2, which was developed for the Seasat A scatterometer [Wentz et al, 1984]. Since the reference height of the SASS 2 model function is 19.5 m, the wind speed is corrected to that at a height of 10 m by multiplying a constant factor of 0.94, which has been commonly used for the conversion.…”
Section: Datamentioning
confidence: 99%
“…The difference between k W92 i and k W92 av is of a different nature; it arises because at a regional level the wind speed distribution departs from the Rayleigh distribution function that was employed when the relationship for long-term winds (k W92 av ) was deconvolved to a relationship for short-term winds (k W92 i ) (Wanninkhof, 1992). The global ocean wind speed distribution can be represented by a Rayleigh distribution function (Wentz et al, 1984), and this implies that the transfer velocities should be scaled with a factor of 1.25 when long-term rather than short-term winds are employed. However, Wanninkhof et al (2002) showed that although this is true on a global basis, there is non-Rayleigh behaviour in many regions so that the correct scaling factor is frequently only 1.1-1.2.…”
Section: Effect Of Using Different K-u 10 Parametrizations On Interanmentioning
confidence: 99%
“…A principal difficulty with any empirical technique is the acquisition of comparison data spanning a sufficiently large range of conditions. The SASS-2 empirical model function developed for the Seasat scatterometer [23], [24] was used to produce the preliminary NSCAT vector wind data set. Although the refined model outlined below addresses systematic errors in the SASS-2 model, the fact that vector winds retrieved from NSCAT data using the SASS-2 model came close to meeting the NSCAT science requirements showed both that SASS-2 properly incorporated the basic speed, direction, and incidence angle modulation of sigma-0 and that the NSCAT sigma-0 measurements were reasonably well calibrated in the absolute sense.…”
Section: A Ku-band Model Function Development and Refinementmentioning
confidence: 99%